MitosRNAs and extreme anoxia tolerance in embryos of the annual killifish Austrofundulus limnaeus - Claire L. Riggs; Steven Cody Woll; Jason E. Podrabsky (Scientific Reports, 2019)
Abstract Embryos of the annual killifish Austrofundulus limnaeus are the most anoxia-tolerant vertebrate. Annual killifish inhabit ephemeral ponds, producing drought and anoxia-tolerant embryos, which allows the species to persist generation after generation. Anoxia tolerance and physiology vary by developmental stage, creating a unique opportunity for comparative study within the species. A recent study of small ncRNA expression in A. limnaeus embryos in response to anoxia and aerobic recovery revealed small ncRNAs with expression patterns that suggest a role in supporting anoxia tolerance. MitosRNAs, small ncRNAs derived from the mitochondrial genome, emerged as an interesting group of these sequences. MitosRNAs derived from mitochondrial tRNAs were differentially expressed in developing embryos and isolated cells exhibiting extreme anoxia tolerance. In this study we focus on expression of mitosRNAs derived from tRNA-cysteine, and their subcellular and organismal localization in order to consider possible function. These tRNA-cys mitosRNAs appear enriched in the mitochondria, particularly near the nucleus, and also appear to be present in the cytoplasm. We provide evidence that mitosRNAs are generated in the mitochondria in response to anoxia, though the precise mechanism of biosynthesis remains unclear. MitosRNAs derived from tRNA-cys localize to numerous tissues, and increase in the anterior brain during anoxia. We hypothesize that these RNAs may play a role in regulating gene expression that supports extreme anoxia tolerance.